2020
DOI: 10.1002/cyto.b.21956
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of B‐cell intracellular signaling by monitoring the PI3K‐Akt axis in patients with common variable immunodeficiency and activated phosphoinositide 3‐kinase delta syndrome

Abstract: Background: Primary antibody deficiencies (PADs) are characterized by hypogammaglobulinemia and impaired B-cell differentiation. Patients with common variable immunodeficiency (CVID) present severe reductions in at least 2 serum immunoglobulins and impaired terminal differentiation of B cells. Most patients with CVID do not appear to present monogenic defects. Activated phosphoinositide 3-kinase delta syndrome (APDS), caused by gain-of-function mutations in the PIK3CD gene (p110δ), can present in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Here, we demonstrated that basal as well as induced PI3K signaling, which regulates the metabolic state, survival, activation and differentiation of this lymphocyte lineage, is severely altered in the naïve B cells of CVID patients. In addition to previous reports [68,69], we found increased baseline but impaired BCR-mediated PI3K pathway activation, especially in the CD21 low B cells of CVID patients, providing potential therapeutic options to target these cells by specific inhibitors of PI3Kδ or mTOR. Altered PI3K signaling may well also contribute to the immunodeficiency in CVID as PI3K signal strength, and the dynamic regulation of transcription factors, such as FOXO1 and HIF1α, determines the selection into short-lived plasmablasts or germinal center B-cell fate, the induction of somatic hyper mutation and class switch recombination and finally the integrity of memory and plasma cell formation [54,55,62,70,71].…”
Section: Discussionsupporting
confidence: 67%
“…Here, we demonstrated that basal as well as induced PI3K signaling, which regulates the metabolic state, survival, activation and differentiation of this lymphocyte lineage, is severely altered in the naïve B cells of CVID patients. In addition to previous reports [68,69], we found increased baseline but impaired BCR-mediated PI3K pathway activation, especially in the CD21 low B cells of CVID patients, providing potential therapeutic options to target these cells by specific inhibitors of PI3Kδ or mTOR. Altered PI3K signaling may well also contribute to the immunodeficiency in CVID as PI3K signal strength, and the dynamic regulation of transcription factors, such as FOXO1 and HIF1α, determines the selection into short-lived plasmablasts or germinal center B-cell fate, the induction of somatic hyper mutation and class switch recombination and finally the integrity of memory and plasma cell formation [54,55,62,70,71].…”
Section: Discussionsupporting
confidence: 67%
“… 1 , 2 , 4 Elevated phosphorylation of AKT (pAKT) and S6K (pS6K) have been found in these patients and are considered valuable indicators of the pathogenic variant in APDS and the hyperactivated PIK/AKT/mTOR/S6K pathway. 6 , 7 , 9 Moreover, in previous studies, patients with APDS who were treated with rapamycin or leniolisib (inhibitors of the PIK/AKT/mTOR/S6K pathway) showed decreased levels of pAKT and pS6K 5 , 9 , 10 Therefore, the pAKT or pS6K levels of the patient in the present case need to be followed up to monitor the efficacy of rapamycin, which may also be a partial supplement for the functional validation of E525G.…”
Section: Discussionmentioning
confidence: 70%
“…A previous study revealed that PIK3CD GOF mutations may result in sustained and exaggerated activation of polyclonal CD8+ T cells; thus, many patients with APDS have increased frequencies of CD8+ T cells. However, these CD8+ T cells seem to exhibit premature immunosenescence and exhaustion, 9 , 12 which reduces their cytotoxicity. PIK3CD GOF mutations also dysregulate the expression of key regulatory molecules and reduce the cytotoxic function of NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Today, several techniques are available in the literature to assess PI3Kδ functionality, including flow cytometry evaluation of intracellular phosphorylation of AKT and S6 in vitro on PBMC, T, B cells and cell lines [ 13 , 21 ]. These functional tests, as well as the analysis of protein levels by means of Western Blot, could also be used during the follow-up of patients to assess the efficacy of the therapy [ 22 , 23 ].…”
Section: Diagnosismentioning
confidence: 99%